Effect of Bolus Position on the Dose of Ionizing Radiation in a Linear Accelerator Simulation - I. N. Chirkova; M. V. Tumilovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The main goal of radiation therapy is to deliver a dose of ionizing radiation to a tumor. When irradiating foci located on the skin surface or at a shallow depth, the problem of overirradiation of healthy tissues arises. In order to optimize the distribution of the dose of ionizing radiation, auxiliary devices in the form of boluses are used in treatment practice. In this case, correct fixation of the bolus, ensuring its tight fit, is of great importance. An increase in the quality of dose distribution with tight fixation of the bolus has been experimentally proven. Numerical values of the dose at the control point with different bolus fit density have been obtained using different methods for calculating irradiation plans.